Zászlódiplomácia -1941 : az 1849-ben orosz kézre került honvédzászlók visszaadása - Olasz, Lajos (Közép-Európai Közlemények, 2013)
During the Russian intervention in 1849, 64 Hungarian military flags were captured by the Russians. Returning the flags was considered several times in the 1920’ies and 1930’ies for exchanging the imprisoned Mátyás Rákosi. However, the Hungarian Government did not want to make any concession to the communist movement and the Soviet Union behind it. As a result of the improvement of the Hungarian-Soviet relationship in 1940, confidential discussions had started about the exchange. Rákosi was released and he left for the Soviet Union. The Soviet Government solemnly returned 56 Hungarian military flags on 24th March 1941. Moscow decided to do this not only in return for Rákosi’s release, but also for foreign policy reasons. Hungary was the only country in the region, which preserved its independence from Germany, where no German troops were staying.